Customer-Centric Service Provider Architecture for the R&E Community - Filiposka, Sonja; Mishev, Anastas; Wein, Frank; Sobieski, Jerry (2016 IEEE International Conference on Cloud Computing Technology and Science (CloudCom), 2016)
The need for customer-centric agile integrated environment offered in an on-demand self-service manner challenges the traditional R&E operations support systems. The service provider architecture proposed in this paper aims to satisfy end-user's requirements by providing a coordinated provisioning of virtualized resources through automation. Empowered by the establishment of open collaborative partnerships it offers expansion of the service catalog with multi-domain solutions based on standardized interoperability between R&E and commercial CSPs. The benefits of the approach are presented via a cloud based case study service that is transformed from a traditional silo to a business process modeled service with added values.

Optimization of an Electromagnetic Actuator using Topology-Optimization - Seebacher, P.; Kaltenbacher, M.; Wein, Frank; Lehmann, H. (2019 22ND INTERNATIONAL CONFERENCE ON THE COMPUTATION OF ELECTROMAGNETIC FIELDS (COMPUMAG 2019), 2019)
CRIS-Team WoS Importer:2020-09-04

Transforming silos to next-generation services - Filiposka, Sonja; Łapacz, Roman; Balcerkiewicz, Michał; Wein, Frank; Sobieski, Jerry (IEEE EUROCON 2017 - 17th International Conference on Smart Technologies, 2017)
The process of transformation leading to a new generation operational and business support systems ensures effectiveness improvements while moving the organization towards a customer centric solution that provides a new wave of services in a multi-domain partner environment. This paper discusses the first steps of this transformational process for the research and educational networks.